Weed control efficiency and productivity in rice-fish-duck integrated farming system. - Nayak, Prafulla Kumar; Panda, Bipin Bihari; Das, Sunil Kumar; Rao, Koroda rajsekhar; Kumar, Upendra; Kumar, Anjani; Munda, Susmita; Satpathy, Bhavani S.; Nayak, Amaresh K. (Indian Journal of Fisheries, 2020)
Rice farming integrated with fish and ducks potentially provides ecological services and supports effective management of weeds which cause rice yield losses due to growth competitiveness with the available resources and productivity. Present study investigated the efficacy of integrating fish and duck in rice farming Â for controlling weed infestations and their impacts on productivity and economics of the system. Appraisal on diversity of weeds indicated that grassy weeds (Echinochola colona, Echinochola crusgalli) and sedges (Cyperus difformis, Cyperus iria, Fimbristylis miliacea) were prevalent in rice during tillering stages, while broad leaf (Ludwigia adscendens, Sphenoclea zeylanica) and aquatic weeds (Marsilia quadrifolia, Otellia alismoides, Vallisneria spiralis, Limnophila indica, Ceratophyllum demersum, Hydrilla verticillata) were abundant during active tillering and panicle initiation stages of rice. A significant reduction in weed density and weed biomass was observed in rice-fish (RF), rice-duck (RD) and rice-fish - duck (RFD) integration. However, weed control efficiency (WCE %) was significantly (p